O USO DO PODER DE COMPRA COMO INSTRUMENTO PARA A PRÁTICA DO DESENVOLVIMENTO SUSTENTÁVEL: ESTUDO DE CASO NO SETOR PÚBLICO - Silva, Ana Luiza (2011)
The present research tried to focus on the need of use the purchasing power of the public administration for the introduction of social and environmental criteria as a way of implementing and expanding the practice of the term "sustainable development". To that end, the research aimed to investigate how a public company performs Sustainable Procurement and how it could improve their method, compared to standards of excellence studied. The research also aimed provide for the legal mechanisms that determine the environmental preservation as a legal principle; showing the ways for purchase products and services at Brazilian Public Administration and the importance of purchasing power; analyze bidding as a way of stimulating sustainable development; verify a possibility of implementing Sustainable Procurement and the benefits that come with this practice. For this purpose, was used case study method for better understand, in practice, objectives of the research. Some questions in the questionnaire were formulated in accordance with the studied methodology. The questionnaire was administered in key sectors: environmental management and supply company. After the results of the case study, it was concluded that the law of bidding does not preclude the practice of Sustainable Public Procurement, on the contrary, the law has as one of its concerns the promotion of sustainable development. In addition, existing laws, in accordance with the provisions contained in the Constitution, are sufficient for the practice of Sustainable Procurement. With the implementation of sustainable bidding, can be purchased sustainable products, also, would be leading the market for green products, still little explored, and encouraging innovation in eco-efficient products, leading to private sector competitiveness and hence falling prices for sustainable products. The implementation of Sustainable Procurement is possible, according to the success studied cases, however, is not always applied in Brazil given its growing phase, for many still think that the law 8.666/93 prevents its practice and is prevented by willingness of the manager.